KARAKTERISTIK MEKANIS BOLT HIGH TENSION LEADS BOEING 737-200 - Utami, Noviana; Sahroni (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2024)
An aircraft engine includes different flow paths, a compressor chamber, a combustion chamber, a turbin chamber, and the exhaust chamber. The hot fluid flow is directed through a second channel past the turbine chamber. The hot fluid flow in the engine includes gas with higher temperature than the ambient temperature outside the engine. Bolt High Tension Leads as insert in the first structural component with the fuselage require good material resistance in the face of plastic deformation. The normal distribution standard of hardness shows 99.7% of the population which is within 3 standard deviations of the average with a fairly high range of hardness values, namely 300 HV. The hardness value of Bolt High Tension Leads functions to resist plastic deformation.